Glucose transporter 4 promotes head and neck squamous cell carcinoma metastasis through the TRIM24-DDX58 axis - Chang, Yu-Chan; Chi, Li-Hsing; Chang, Wei-Ming; Su, Chia-Yi; Lin, Yuang-Feng; Chen, Chi-Long; Chen, Ming-Huang; Chang, Peter Mu-Hsin; Wu, Alex T. H.; Hsiao, Michael (Journal of hematology and oncology, 2017)
Head and neck squamous cell carcinoma (HNSCC) represents a unique and major health concern worldwide. Significant increases in glucose uptake and aerobic glycolysis have been observed in HNSCC cells. Glucose transporters (GLUTs) represent a major hub in the glycolysis pathway, with GLUT4 having the highest glucose affinity. However, GLUT4's role in HNSCC has not been fully appreciated. An in silico analysis was performed in HNSCC cohorts to identify the most significant glucose transporter associated with HNSCC patient prognosis. An immunohistochemical analysis of a tissue microarray with samples from 90 HNSCC patients was used to determine the association of GLUT4 with prognosis. Complementary functional expression and knockdown studies of GLUT4 were performed to investigate whether GLUT4 plays a role in HNSCC cell migration and invasion in vitro and in vivo. The detailed molecular mechanism of the function of GLUT4 in inducing HNSCC cell metastasis was determined. Our clinicopathologic analysis showed that increased GLUT4 expression in oral squamous cell carcinoma patients was significantly associated with a poor overall survival (OS, P = 0.035) and recurrence-free survival (RFS, P = 0.001). Furthermore, the ectopic overexpression of GLUT4 in cell lines with low endogenous GLUT4 expression resulted in a significant increase in migratory ability both in vitro and in vivo, whereas the reverse phenotype was observed in GLUT4-silenced cells. Utilizing a GLUT4 overexpression model, we performed gene expression microarray and Ingenuity Pathway Analysis (IPA) to determine that the transcription factor tripartite motif-containing 24 (TRIM24) was the main downstream regulator of GLUT4. In addition, DDX58 was confirmed to be the downstream target of TRIM24, whose downregulation is essential for the migratory phenotype induced by GLUT4-TRIM24 activation in HNSCC cells. Here, we identified altered glucose metabolism in the progression of HNSCC and showed that it could be partially attributed to the novel link between GLUT4 and TRIM24. This novel signaling axis may be used for the prognosis and therapeutic treatment of HNSCC in the future.